Online Learning Strategy for PAI Mapel during the Covid-19 Pandemic at Senior High School : Strategi Pembelajaran Daring Mapel PAI pada Masa Pandemi Covid-19 di Sekolah Menengah Pertama - Ramadhania Grafika Putri; Istikomah Istikomah (Universitas Muhammadiyah Sidoarjo, 2022)
Online Learning Strategy is a learning system planning that is not done face-to-face but uses a platform that can help the teaching and learning process even though it is distanced that is systematically arranged to achieve success and success in achieving its goals. during the current Covid-19 Pandemic in order to provide easy access for students to seek knowledge even though they are at home. This study aims to (1) determine the online learning strategy for PAI subjects during the Covid-19 pandemic at SMAN 1 Sidoarjo. The type of research used in this study is a qualitative research with students of SMAN 1 Sidoarjo, PAI teachers at SMAN 1 Sidoarjo and principals of SMAN 1 Sidoarjo, using a phenomenological approach, types and sources of qualitative and quantitative data. The data collection technique is (1) interview (2) observation (3) documentation. The data analysis technique used descriptive qualitative data analysis techniques and the research results were described in words so as to obtain conclusions. Based on the research that has been done, there are several research results, namely: (1) PAI learning strategies during the normal period at SMAN 1 Sidoarjo using contextual, cooperative and independent learning strategies